Design of a Guided Internet- and Mobile-Based Intervention for Internet Use Disorder—Study Protocol for a Two-Armed Randomized Controlled Trial - Saruhanjan, Karina; Zarski, Anna-Carlotta; Schaub, Michael Patrick; Ebert, David Daniel (Frontiers in Psychiatry, 2020)
Context: Internet Use Disorder (IUD), characterized as the inability to control one’s internet use, is emerging as an increasing societal concern as it is associated with reduced quality of life and mental health comorbidities. Evidence-based treatment options are, however, scarce due to the novelty of the diagnosis. Internet- and mobile-based interventions may be an effective means to deliver psychological treatment to individuals with IUD as they address individuals affected in their online setting. The aim of the study is to evaluate the efficacy of a newly developed, guided internet- and mobile-based intervention for IUD. Methods: In a two-armed randomized controlled trial (N = 130), individuals showing problematic internet use patterns (Internet Addiction Test ≥ 49) will be randomly allocated to the internet- and mobile-based intervention or a waiting control group. Assessments will take place at baseline, 7 weeks, 6- and 12 months after randomization. The primary outcome is internet addiction symptom severity (IAT) at 7 weeks. Secondary outcomes include quality of life, depressive symptoms, anxiety, and other psychosocial variables associated with IUD. Intervention: The intervention consists of seven sessions: Goal setting and motivational interviewing, impulse control, problem solving, cognitive restructuring, self-worth, relapse prevention, and a booster session. Participants are supported by an eCoach who provides individual feedback after completion of each session. Participants can choose between several elective sessions based on individual need. Conclusions: This is the first study to evaluate an internet- and mobile-based intervention for IUD, which could be a promising first step to reduce individuals’ disease burden.